Survey of mobile ad hoc networks (manets) (International Journal of Engineering and Computer Science, 2019)
Mobile Ad Hoc Network (MANET) is the one of the type of ad hoc network, the MANET is a collection of two or more devices or nodes or terminals with wireless communications and networking capability that communicate with each other without the aid of any centralized  administrator also the wireless nodes that can dynamically form a network to exchange information without using any existing fixed network infrastructure. And it's an autonomous system in which mobile hosts connected by wireless links are free to be dynamically and sometime act as routers at the same time, In MANET, the mobile nodes require to forward packets for each other to enable communication among nodes outside of transmission  range. The nodes in the network are free to move independently in any direction, leave and join the network arbitrarily. Thus a node experiences changes in its link states regularly with other devices. Eventually, the mobility in the ad hoc network, change of link states and other properties of  wireless transmission such as attenuation, multipath propagation, interference etc. This paper discuses   study of Mobile ad-hoc Networks (MANET): classification, characteristics, structure of  MANET  and challenges that are imposed by Mobile ad-hoc Networks.